(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2024)
The purpose of this study was to determine the effectiveness and obstacles in using Colorful Sticky Notes media in teaching reading. This study uses a quantitative method with a class action research approach (CAR). The result of this research is the implementation of effectiveness and obstacles in using Colorful Sticky Notes media. The results of this study indicate the effectiveness of using Colorful Sticky Notes media in teaching reading. Colorful Sticky Notes media is an effective media used to get students excited about learning to read. There are also several reasons students are motivated during the learning process. The average score of students’ ability to use Colorful Sticky Notes media increased from 58.82 to 84.68, and passed the minimum mastery curriculum where 100% of students achieved this score.